Testing predictions of the Janzen–Connell hypothesis: a meta‐analysis of experimental evidence for distance‐ and density‐dependent seed and seedling survival. (July 2014) - Comita, Liza S.; Queenborough, Simon A.; Murphy, Stephen J.; Eck, Jenalle L.; Xu, Kaiyang; Krishnadas, Meghna; Beckman, Noelle; Zhu, Yan; Gómez‐Aparicio, Lorena
Summary The Janzen–Connell hypothesis proposes that specialist natural enemies, such as herbivores and pathogens, maintain diversity in plant communities by reducing survival rates of conspecific seeds and seedlings located close to reproductive adults or in areas of high conspecific density. Variation in the strength of distance‐ and density‐dependent effects is hypothesized to explain variation in plant species richness along climatic gradients, with effects predicted to be stronger in the tropics than the temperate zone and in wetter habitats compared to drier habitats. We conducted a comprehensive literature search to identify peer‐reviewed experimental studies published in the 40+ years since the hypothesis was first proposed. Using data from these studies, we conducted a meta‐analysis to assess the current weight of evidence for the distance and density predictions of the Janzen–Connell hypothesis. Overall, we found significant support for both the distance‐ and density‐dependent predictions. For all studies combined, survival rates were significantly reduced near conspecifics compared to far from conspecifics, and in areas with high densities of conspecifics compared to areas with low conspecific densities. There was no indication that these results were due to publication bias. The strength of distance and density effects varied widely among studies. Contrary to expectations, this variation was unrelated to latitude, and there was no significant effect of study region. However, we did find a trend for stronger distance and density dependence in wetter sites compared to sites with lower annual precipitation. In addition, effects were significantly stronger at the seedling stage compared to the seed stage. Synthesis. Our study provides support for the idea that distance‐ and density‐dependent mortality occurs in plant communities world‐wide. Available evidence suggests that natural enemies are frequently the cause of such patterns, consistent with the Janzen–Connell hypothesis, but additional studies are needed to rule out other mechanisms (e.g. intraspecific competition). With the widespread existence of density and distance dependence clearly established, future research should focus on assessing the degree to which these effects permit species coexistence and contribute to the maintenance of diversity in plant communities.